Improving the Shear Strength of Lightweight RC Thick Hollow Core Slab Made of Recycled Materials - Nassif Sabr, Yousif; Husain Khalaf Jarallah, Dr.; Hassan Issa Abdul Kareem, Dr. (International Journal of Engineering and Technology, 2018)
This research paper focused on the experimental study about shear behavior of reinforced concrete thick hollow core slab. The reduction hollow length technique was used to resist the shear failure that occurred in the thick hollow core slab. The three hollows were used in tested slabs. The effect of reduction in the length of hollow in the shear region as well as the sides hollow was considered in the shear behavior of the tested hollow core slab. The recyclable material was used to a get of lightweight concrete, where the crushed clay brick was used as a coarse aggregate instead of the gravel. The test was done by applying two line load. The specimens were tested up to failure. The experimental results showed an increase in the shear strength up to 109.52% and an increase in the deflection up to 24% compared with the hollow core slab specimen that all hollow core is accessible. From the experimental result of this investigation can avoid the shear failure subsequently the load devolves from the shear region to the flexural region with change the mode of failure from shear failure to flexural-shear failure.Â Â Â